슈퍼 히어로 피규어의 외형적 시각요소 평가에 따른 구매의도 - 김준수(Jun-Su Kim) (디지털콘텐츠학회논문지, 2017)
슈퍼 히어로 영화는 모든 세대를 아우를 수 있는 새로운 장르 컨벤션을 형성하였다. 영상콘텐츠에서 파생된 피규어는 전문적인 조형기술을 통해 제작된 입체 조형물이다. 피규어에 대한 소유는 가상과 현실을 연결시켜 주는 매개체로써 상징적 의미를 가진다. 이러한 관점에서 피규어는 콘텐츠 산업의 시장 확장에 따른 파생된 캐릭터 상품으로써 중요한 부분을 차지한다. 이러한 맥락에서 본 연구는 슈퍼히어로 피규어의 외형적 시각요소 평가가 구매의도에 어떠한 영향을 미치는가를 분석함으로써 소비자구매형태를 확인하는 것이 그 목적이다. 이를 위해 독립변인을 캐릭터의 외형적 시각요소 평가로써 색상, 신체유형, 얼굴모양, 동작으로, 종속변인은 구매의도로 하여 다중회귀분석을 실시하였다. 분석결과, 색상, 신체유형, 얼굴모양은 구매의도에 긍정적 영향을 미치는 것으로 나타났고, 동작은 구매의도에 유의미한 영향력이 없는 것으로 나타났다. Superhero films have formed a new genre convention encompassing all the generations. Figures derived from image contents are solid figures produced by means of professional figuration skills. Possession of figures has a symbolic meaning as a medium connecting the imaginary world and real one. From this perspective, figures hold an important position as a character product derived due to market expansion of the content industry. In this context, the study, which analyzed how appraisal of outward visual elements in superhero action figures might affect consumer's purchase intention, aimed to identify their purchase patterns. For this, the study established colors, types of physical body, facial figures and motions as independent variables for appraisal of outward visual elements, and purchase intention as a dependent variable and then conducted a multiple regression analysis. As a result of the analysis, the study found that colors, types of physical body and facial figures had a positive influence on purchase intention, while motions had no significant influence. KCI Citation Count: 4